Performance Based Behavior of Reinforced Concrete Frames Designed According to Iraqi Seismic Code - Ameer Hameed Eliwi; Ali Naji Attiyah (Genius Journals, 2023)
The objectives of this study was to develop and document a method for accurately assessing building system performance and response parameters for use in seismic design for typical reinforced concrete (RC) moment-resisting frames (MRFs), then compare the R factor derived with the values stated in the Iraqi seismic code of practice. The effect of the following parameters on the archetype models has studied: number of stories, bay width, the building stiffness represent by f'c, Seismic design category. The results indicate that the general trend in increasing the bay width to increase the value of seismic performance factors is to increase. While the value of seismic performance factors decreased when increasing the building height.
Keywords: increasing; studied; performance